2008
DOI: 10.1073/pnas.0806858105
|View full text |Cite
|
Sign up to set email alerts
|

CYCLOPS, a mediator of symbiotic intracellular accommodation

Abstract: The initiation of intracellular infection of legume roots by symbiotic rhizobia bacteria and arbuscular mycorrhiza (AM) fungi is preceded by the induction of calcium signatures in and around the nucleus of root epidermal cells. Although a calcium and calmodulin-dependent kinase (CCaMK) is a key mediator of symbiotic root responses, the decoding of the calcium signal and the molecular events downstream are only poorly understood. Here, we characterize Lotus japonicus cyclops mutants on which microbial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
443
4
12

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 432 publications
(487 citation statements)
references
References 48 publications
16
443
4
12
Order By: Relevance
“…We also tested the T265D substituted form of CCaMK 314 , designated CCaMK 314 TD . Analysis in L. japonicus revealed that green fluorescent protein (GFP)-fused CCaMK is localized in the nucleus (Yano et al, 2008), although there is no canonical NLS in CCaMK. However, GFP-fused CCaMK 314 TD was found both in the cytosol and in the nucleus of leaf epidermal cells of Nicotiana benthamiana (see Supplemental Figures 2A to 2C online), indicating that these proteins had lost the ability to specifically localize to the nucleus.…”
Section: Nuclear Localization Of Deregulated Ccamk Strongly Induced Bmentioning
confidence: 99%
See 1 more Smart Citation
“…We also tested the T265D substituted form of CCaMK 314 , designated CCaMK 314 TD . Analysis in L. japonicus revealed that green fluorescent protein (GFP)-fused CCaMK is localized in the nucleus (Yano et al, 2008), although there is no canonical NLS in CCaMK. However, GFP-fused CCaMK 314 TD was found both in the cytosol and in the nucleus of leaf epidermal cells of Nicotiana benthamiana (see Supplemental Figures 2A to 2C online), indicating that these proteins had lost the ability to specifically localize to the nucleus.…”
Section: Nuclear Localization Of Deregulated Ccamk Strongly Induced Bmentioning
confidence: 99%
“…Indeed, previous studies have identified symbiosis mutants in legume plants that abolish both AMS and RNS. Several such symbiosis (Sym) genes have been identified through studies of these mutants (Endre et al, 2002;Stracke et al, 2002;Ané et al, 2004;Lé vy et al, 2004;ImaizumiAnraku et al, 2005;Kanamori et al, 2006;Tirichine et al, 2006;Saito et al, 2007;Yano et al, 2008;Groth et al, 2010;Murray et al, 2011). A signaling pathway composed of these symbiosis genes is termed the "common Sym pathway" (Parniske, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, LYK3 is thought to mediate bacterial entry into root hairs (Catoira et al, 2001;Limpens et al, 2003;Smit et al, 2007). Downstream components of the NF signal transduction pathway in M. truncatula include DMI2, a leucine-rich repeat receptor kinase (Esseling et al, 2004), DMI1, a potassium ion channel (Ané et al, 2004;Riely et al, 2007), NENA, a nuclear pore component (Groth et al, 2010), CCaMK/DMI3, a Ca 2+ and calmodulin-dependent protein kinase (Lévy et al, 2004;Mitra et al, 2004), the CCaMK-regulated transcriptional regulator CY-CLOPS/IPD3 (Messinese et al, 2007;Yano et al, 2008;Singh et al, 2014), and various transcriptional regulators such as NSP1, NSP2, ERN1, and NIN (Kaló et al, 2005;Smit et al, 2005;Marsh et al, 2007, Middleton et al, 2007. As a consequence of NF signaling, the expression of many symbiotic genes such as the early nodulin gene ENOD11 is induced (Andriankaja et al, 2007;Hirsch et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These include DOESN'T MAKE INFECTIONS1 (DMI1), DMI2, and DMI3, two nucleoporins, and the DMI3-interacting protein IPD3/CYCLOPS (Messinese et al, 2007;Yano et al, 2008). DMI2 (SYMRK in L. japonicus) encodes a Leu-rich repeat (LRR)-RLK required for calcium spiking and subsequent transmission of the Nod factor signal (Endre et al, 2002;Stracke et al, 2002).…”
mentioning
confidence: 99%